2005
DOI: 10.1021/jo050883i
|View full text |Cite
|
Sign up to set email alerts
|

Structural Effects on the β-Scission Reaction of Tertiary Arylcarbinyloxyl Radicals. The Role of α-Cyclopropyl and α-Cyclobutyl Groups

Abstract: A product and time-resolved kinetic study on the reactivity of tertiary arylcarbinyloxyl radicals bearing alpha-cyclopropyl and alpha-cyclobutyl groups has been carried out. Both the 1-cyclopropyl-1-phenylethoxyl (1.) and alpha,alpha-dicyclopropylphenylmethoxyl (2.) radicals undergo beta-scission to give cyclopropyl phenyl ketone as the major or exclusive product with rate constants higher than that measured for the cumyloxyl radical. It is proposed that in the transition state for beta-scission of 1. and 2., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 43 publications
8
34
1
Order By: Relevance
“…The same effect was found for alkyloxyl radicals . Bietti et al also confirmed this effect and found that the solvent Dimroth‐Reichardt parameter ( E T ) correlated well with the increase in rate, confirming earlier results by the Ingold group, see Figure . The E T parameter represents the charge‐transfer absorption of the solvent in pyridinium N ‐phenolbetaine and serves as a different measure of solvent polarity than the dielectric constant .…”
Section: Kinetic Solvent Effects Within Reaction Familiessupporting
confidence: 76%
“…The same effect was found for alkyloxyl radicals . Bietti et al also confirmed this effect and found that the solvent Dimroth‐Reichardt parameter ( E T ) correlated well with the increase in rate, confirming earlier results by the Ingold group, see Figure . The E T parameter represents the charge‐transfer absorption of the solvent in pyridinium N ‐phenolbetaine and serves as a different measure of solvent polarity than the dielectric constant .…”
Section: Kinetic Solvent Effects Within Reaction Familiessupporting
confidence: 76%
“…In isooctane, MeCN and tert-alkanol solution, CumO • is characterized by a broad absorption band in the visible region of the spectrum centered at 485 nm, 32,33 the position of which is red-shifted in MeCN/H 2 O 2:1, 33 MeOH, 34 and TFE. 35 Under these conditions, CumO • decays mainly by C−CH 3 β-scission, with the exception of the experiments carried out in MeOH solution where hydrogen atom abstraction from the solvent becomes the predominant reaction. 34 The time-resolved absorption spectra observed after reaction of CumO • with phenol in MBOH and TFE are displayed in the Supporting Information (Figures S1 and S2, respectively).…”
Section: ■ Resultsmentioning
confidence: 97%
“…Then, the single electron transfer (SET) between intermediate E and Cu(I) results in alkoxy radical F . Eventually, highly selective β‐scission of the carbon‐carbon of the intermediate F would lead to the final product 3aa along with the benzyl radical G , [ 15 ] which could react with oxygen or sulfonyl radical C leading to the corresponding aldehyde I and radical‐radical coupling molecule K . Notably, the oxygen atom of carbonyl group of 3aa could undergo reversible oxygen atom exchange with water.…”
Section: Resultsmentioning
confidence: 99%